THEORY CONCEPT OF DOROTHEA ELIZABETH OREM'S NURSING MODEL: IN NURSING CARE FOR TYPE 2 DIABETES MELLITUS - Hidayanti, Putri; Nursanti, Irna (JOURNAL EDUCATIONAL OF NURSING(JEN), 2025)
Type 2 Diabetes Mellitus requires long-term management and patient involvement in self-care. Dorothea Elizabeth Orem's Self Care Theory provides a comprehensive approach to facilitating patient independence through identifying self-care needs, self-care agency capabilities, and determining appropriate nursing systems. This study aims to provide a comprehensive overview of the conceptual model and theory of Dorothea Elizabeth Orem and analyze the application of Orem's theory in nursing care for type 2 diabetes mellitus patients through a case study on Mrs. S, a patient with poor blood sugar control, non-adherence to medication, dietary ignorance in diabetics, and difficult-to-heal foot wounds. The research method uses a case study approach, through requisites assessment, self-care deficit identification, nursing system determination, and the preparation of interventions based on SIKI-SLKI standards. The results show that Mrs. S experiences knowledge deficits, ineffective health management and infection risks. The nursing system required includes supportive-educational and partly compensatory systems. The interventions provided improved patient understanding, medication adherence, wound care, and general self-care skills. The application of Orem's theory has been shown to provide a systematic framework for improving the independence of patients with Type 2 DM and preventing complications.